A preliminary biomechanical study on trachea reconstruction surgery using the clavicular periosteum - Zhu, Xiaoli; Sun, Kangli; Xia, Xin; Chen, Yu; Sun, Anqiang; Chen, Xingming (Frontiers in Bioengineering and Biotechnology, 2023)
The clavicular periosteum is a suitable material for trachea reconstruction. However, because the periosteum is softer and has different mechanical properties than tracheal cartilage, the mechanical loads under physiological conditions after trachea reconstruction may cause collapse or stenosis of the repaired trachea. In this study, the mechanical properties of the clavicular periosteum were tested, and the 3D trachea geometry was constructed based on CT-scanning images acquired before the surgery. Differing degrees of stenosis (0%, 33%, and 55%) for the repaired trachea sections were predetermined, presenting the different degrees of the tracheal cross-sectional area immediately after clavicular periosteum reconstruction. Then the biomechanical environments of the trachea and the airflow were simulated and analyzed. In the fluid mechanics simulation, the air pressure on the patch area decreased with increasing degrees of stenosis, while the fluid velocity increased as stenosis increased. In solid mechanics simulations, patch area deformation increased as the cross-sectional area of the trachea decreased, and the stress in the patch increased as stenosis increased. This may cause tissue remodeling, thickening, and scarring of the patch area. The mechanical changes in the repaired trachea would further aggravate the stenosis. This preliminary study provides a biomechanical understanding of tracheal repair surgery that could help explain some post-operative complications and inform decisions regarding surgical approaches.